The Influence of Online Advertising on the Consumer Behavior of Smartphone Customers - Alicia Sulayon; Jocelyn S Emotin (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The fundamental purpose of the study was to determine which domain of the online advertising significantly influence consumer buying behavior. Design/methodology/approach: This study employed a quantitative non-experimental research design utilizing correlational technique. The survey was conducted at Tagum City, Davao del Norte, Philippines. A total of 365 customers participated in this study. Findings: Results revealed that online advertising is much evident as perceived by the customers. On the other hand, the consumer buying behavior towards purchasing smartphones is much observed. The statistical result further revealed that there was a significant relationship between online advertising and consumer buying behavior of smartphone customers. Research limitations/implications: There are only two variables considered in this paper: Online advertising and consumer buying behavior; Intervening variables are not considered and the sample for this study is 365 using a random sampling method. Practical implications: Among the five indicators, stimulation, brand recall, and necessity were found to have significantly predicted consumer buying behavior in purchasing smartphones. Originality/value: This paper is a collaborative effort of the researchers to understand consumer behavior of smartphone customers relative to online advertising. Paper type: Research paper